Positive electrode sheet and secondary battery
Through the introduction of decentralized agents and cross -linking structures in the positive material layer, the three -dimensional space network cross -linking structure is formed, and the problem of insufficient peeling strength and internal agglomeration when the existing positive chipping is improving the energy density, and the higher battery life and life. Energy density.
Patent Information
- Application Number
- CN202411442380.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-16
AI Technical Summary
While the existing positive electrode sheets increase the energy density of the battery, it is difficult to ensure the peel strength and cohesion of the electrode sheets, especially under thick electrode designs.
Through the introduction of dispersant and cross -linked structures in the positive material layer, a chemical bond combined with the surface of the decentralized agent and the surface of the streaming body, and forming a three -dimensional space network cross -linking structure through the cross -linked agent to increase Kiddo.
The peeling strength and internal agglomeration of the polar film are improved, the cycle life of the battery is extended, and the energy density of the battery is increased under the design of the thick electrode.
Smart Images

Figure CN118969959B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a positive electrode sheet and a secondary battery. Background Art
[0002] Secondary batteries have the advantages of high voltage, high specific energy, stable discharge voltage, good cycle performance, good safety performance, and long service life. They are widely used in power vehicles, energy storage and other fields. Lithium-ion batteries in secondary batteries include lithium iron phosphate systems. Lithium iron phosphate (LFP) batteries are the mainstream system for energy storage and power batteries because of their advantages such as good safety, long cycle life and low cost. However, the LFP battery system is limited by the material structure and voltage platform, resulting in its low energy density. The method of improving the energy density of LFP batteries in the prior art is usually to adopt a thick electrode design, but the thick electrode design has high requirements for the peeling strength and cohesion of the pole piece. In the existing pole piece, a higher proportion of binder is usually added to the positive electrode slurry to increase the peeling strength of the pole piece, but the increase in the binder content will lead to a decrease in the battery energy density and deteriorate other battery properties.
[0003] Therefore, how to design a positive electrode sheet to improve the battery energy density while ensuring the peel strength and cohesion of the electrode sheet under the thick electrode design is an urgent problem to be solved. Summary of the invention
[0004] The present invention aims at the problem that the existing positive electrode sheet cannot ensure the peeling strength and cohesion of the electrode sheet while improving the battery energy density. The present invention provides a positive electrode sheet and a secondary battery.
[0005] In order to solve the above technical problems, the present invention provides a positive electrode sheet, the positive electrode sheet comprising a current collector and a positive electrode material layer, the positive electrode material layer being arranged on at least one side of the current collector;
[0006] The positive electrode material layer includes a positive electrode active material, a first conductive agent, a dispersant and a cross-linking structure, wherein the dispersant is wrapped on the surface of the positive electrode active material and the conductive agent, and the cross-linking structure is used for chemical bonding between the dispersants and chemical bonding between the dispersants and the surface of the current collector.
[0007] Preferably, the surface of the current collector is modified with a silane coupling agent containing double bonds;
[0008] The silane coupling agent containing double bonds includes one or more of (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane, 3-(trimethoxysilyl)propyl acrylate, vinyltrimethoxysilane, and allyltrimethoxysilane.
[0009] Preferably, the current collector comprises a current collector body and a conductive coating, wherein the conductive coating is disposed on at least one side of the current collector body, and the conductive coating comprises a second conductive agent, and the surface of the second conductive agent is modified with the silane coupling agent containing double bonds.
[0010] Preferably, the end group of the dispersant is an acrylate group, and the end group and the silane coupling agent containing a double bond are respectively combined with a cross-linking agent to form the cross-linking structure.
[0011] Preferably, the dispersant comprises a polymer segment and an anchoring group connected to the polymer segment, the polymer segment comprises an acrylate-polyol unit, and the end group of the polymer segment is an acrylate group; the anchoring group comprises one or more of a nitrile group, an amide group, an ester group, a carboxyl group and a hydroxyl group.
[0012] Preferably, the dispersant is obtained by reacting a raw material composition comprising an acrylate-polyol monomer and an anchor group-containing monomer.
[0013] Preferably, the molar ratio of the anchor group-containing monomer to the acrylate-polyol monomer is (10-50): (20-70).
[0014] Preferably, the molecular weight of the polymer chain segment is 10000-20000 g / mol.
[0015] Preferably, the crosslinking agent contains at least three acrylate groups in its structure.
[0016] Preferably, the cross-linking agent includes at least one of pentaerythritol tetraacrylate and pentaerythritol triacrylate.
[0017] Preferably, the mass of the dispersant accounts for 0.1% to 0.3% of the solid mass in the positive electrode material layer;
[0018] And / or, the molar ratio of the crosslinking agent to the dispersant is (0.1-0.3):1.
[0019] In a second aspect, the present application provides a secondary battery, comprising a negative electrode sheet, an electrolyte, and the positive electrode sheet as described above.
[0020] Beneficial Effects
[0021] In the positive electrode sheet of the present application, the dispersant and the current collector surface are combined through the cross-linking structure, and the dispersants are cross-linked with each other, thereby increasing the bonding force between the conductive coating and the positive electrode material layer, further improving the peel strength and cohesion of the electrode sheet, and improving the cycle life of the battery. At the same time, under the premise of a thick electrode design for the positive electrode sheet, the energy density of the battery is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic structural diagram of a positive electrode sheet provided in one embodiment of the present invention. DETAILED DESCRIPTION
[0023] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0024] An embodiment of the present application provides a positive electrode sheet, the positive electrode sheet comprising a current collector and a positive electrode material layer, the positive electrode material layer being arranged on at least one side of the current collector;
[0025] The positive electrode material layer includes a positive electrode active material, a first conductive agent, a dispersant and a cross-linking structure, wherein the dispersant is wrapped on the surface of the positive electrode active material and the conductive agent, and the cross-linking structure is used for chemical bonding between the dispersants and chemical bonding between the dispersants and the surface of the current collector.
[0026] Specifically, the positive electrode active material may be various positive electrode active materials commonly used in the art, such as lithium iron phosphate (LFP). The first conductive agent may be various conductive agents commonly used in the art, such as carbon nanotubes (CNTs), conductive carbon black (SP) or conductive graphite (KS-6). The current collector may be aluminum foil or a composite current collector.
[0027] like Figure 1 As shown, during the baking and drying process after the positive electrode material layer is coated with the conductive coating 2, the acrylate units on the surface of the dispersant and the conductive agent surface modified by the coupling agent with double bonds in the current collector conductive layer undergo thermal crosslinking, generating crosslinking points and forming a three-dimensional network crosslinking structure, which increases the bonding force between the conductive coating 2 and the positive electrode material layer, further improves the peel strength and cohesion of the electrode sheet, and increases the cycle life of the battery. At the same time, the thick electrode (single-sided surface density 300g / m 2 , compacted density 2.5g / cm 3 ) design, improve the energy density of the battery.
[0028] The silane coupling agent containing double bonds includes one or more of (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane, 3-(trimethoxysilyl)propyl acrylate, vinyltrimethoxysilane, and allyltrimethoxysilane.
[0029] Furthermore, if Figure 1As shown, in some embodiments, the current collector includes a current collector body 1 and a conductive coating 2, the conductive coating 2 is arranged on both sides of the current collector, and the conductive coating 2 includes a second conductive agent, and the surface of the second conductive agent is modified with the silane coupling agent containing double bonds. The second conductive agent can be various conductive agents commonly used in the art, for example, carbon nanotubes (CNTs), conductive carbon black (SP) or conductive graphite (KS-6).
[0030] The preparation method of carbon-coated aluminum foil is as follows:
[0031] Add 50 parts of ethanol and 50 parts of deionized water, add 10 parts of SP and stir at a low speed of 20 rpm for 10 minutes, then add 0.02 parts of silane coupling agent, transfer the dispersion to a sand mill and sand grind for 1 minute, then add polyacrylate binder (solid content 10%), stir at a low speed of 20 rpm for 2 minutes, and sand grind for 2 hours. The prepared conductive slurry is coated on the surface of aluminum foil, and carbon-coated aluminum foil is obtained after drying.
[0032] In some embodiments, the end group of the dispersant is an acrylate group, and a cross-linking agent is added to allow the acrylate at the end of the dispersant to polymerize itself or cross-link with the SP modified with a double-bonded silane coupling agent in the conductive coating through the action of the cross-linking agent to form a three-dimensional cross-linked network structure, which can improve the cohesive force of the coating formed by the positive electrode, thereby improving the peeling force, further improving the flexibility of the electrode, and avoiding material falling during winding or die-cutting of the electrode.
[0033] Specifically, Figure 1 As shown, the cross-linking agent acts between the dispersants and between the dispersants and the conductive agent modified by the silane coupling agent with double bonds to form cross-linking points, further forming a three-dimensional cross-linked network structure, thereby improving the cohesive force of the coating formed by the positive electrode.
[0034] In some embodiments, the dispersant comprises a polymer segment and an anchoring group connected to the polymer segment, wherein the polymer segment comprises an acrylate-polyol unit, and the terminal group of the polymer segment is an acrylate group. The anchoring group comprises one or more of a nitrile group, an amide group, an ester group, a carboxyl group, and a hydroxyl group.
[0035] The dispersant provided in this embodiment has a polymer segment and an anchoring group, which overcomes the van der Waals attraction between lithium iron phosphate and conductive agent particles through the polymer segment, reduces the viscosity effect caused by small particles of LFP and conductive agent, thereby increasing the solid content of the positive electrode slurry, improving the coating yield and improving the coating efficiency. The dispersant provided in this embodiment contains an acrylate group, which can improve the cohesion of the coating formed by the positive electrode slurry through self-polymerization or interaction with other double-bonded groups in the positive electrode material layer, and further improve the peeling force of the positive electrode sheet.
[0036] In some embodiments, the dispersant is obtained by reacting a raw material composition comprising an acrylate-polyol monomer and an anchor group-containing monomer.
[0037] Preferably, the acrylate-polyol monomer contains two or more acrylate groups.
[0038] Specifically, the acrylate-polyol monomer has acrylate groups at both ends, wherein the acrylate group at one end reacts with the anchor group monomer, and the acrylate group at the other end can be used for self-polymerization and to react with the conductive agent in the conductive coating modified by the double-bond silane coupling agent.
[0039] In some embodiments, the molar ratio of the anchor group-containing monomer to the acrylate-polyol monomer is (10-50): (20-70).
[0040] Specifically, the molar ratio of the anchor group-containing monomer to the acrylate-polyol monomer includes, but is not limited to, 10:20, 10:70, 30:50, 30:20, 30:70, 50:20, 50:50 or 50:70.
[0041] In some embodiments, the acrylate-polyol monomers include one or more of poly(ethylene glycol) diacrylate, polyethylene glycol dimethacrylate, polyethylene glycol-block-polypropylene glycol-block-polyethylene glycol diacrylate, and poly(propylene glycol) dimethacrylate. By selecting the above-mentioned acrylate-polyol monomers, it is convenient to control the length and steric hindrance of the polymer chain segments in the dispersant, thereby adjusting the dispersion effect.
[0042] In a preferred embodiment, the molecular weight of the acrylate-polyol monomer is 10,000-20,000 g / mol, and the Tg of the dispersant is 25°C-45°C. By regulating the molecular weight of the polymer segment and thus the chain length of the polymer segment, on the one hand, the van der Waals attraction between lithium iron phosphate and conductive carbon black is overcome, thereby adjusting the dispersing properties of the dispersant. On the other hand, the glass transition temperature of the formed dispersant is regulated. T g , to improve the flexibility of the pole piece.
[0043] If the molecular weight of the polymer chain segment is too small, the anchoring group in the dispersant will have a "bridging" effect, and the purpose of dispersing lithium iron phosphate and conductive carbon black cannot be achieved. At this time, Tg is higher than 45°C.
[0044] If the molecular weight of the polymer chain segment is too large, the polymer molecules of the dispersant are easy to fold back on themselves, forming a large steric hindrance, causing the slurry to flocculate, making the dispersion effect of the final positive electrode slurry poor, and the Tg is lower than 25°C.
[0045] The molecular weight of the polymer chain segment is in the range of 10,000-20,000 g / mol, which can avoid the "bridging" effect of the anchoring group in the dispersant and T g The temperature is relatively moderate, which is 25℃~45℃, so as to achieve better reinforcement effect and better flexibility.
[0046] In some embodiments, the anchoring group-containing monomer includes one or more of acrylonitrile, methacrylonitrile, acrylamide, bisacrylamide, cyanoacetamide, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, lauryl acrylate, isobutyl acrylate, tert-butyl acrylate, octadecyl acrylate, phenyl methacrylate, n-hexyl acrylate, stearic methacrylate, ethylene glycol, and ethylene glycol monomethyl ether. On the one hand, the introduction of anchoring groups can improve the wettability of the electrode and the electrolyte, thereby reducing the internal resistance of the battery and improving the performance of the battery cell. On the other hand, the anchoring group reacts with the modifying unit to form a covalent bond or an ionic bond to enhance the adhesion between the conductive coating 2 and the positive electrode material layer, thereby improving the peel strength of the electrode.
[0047] Furthermore, the dispersant can be obtained by conventional double bond polymerization reaction, and the specific reaction conditions are easily known to those skilled in the art. For example, the preparation method includes the following steps:
[0048] Mix ethanol as a solvent, an anchor group-containing monomer, and an acrylate-polyol monomer under nitrogen, and stir to obtain a mixed solution;
[0049] The mixed solution was heated to 50-80° C. under a nitrogen atmosphere, and then an initiator, azobisisobutyronitrile, was added, and the mixture was kept warm with continuous stirring. The reaction was stopped after 24 hours of reaction, and then the ethanol was removed by heating and rotary evaporation to obtain a dispersant.
[0050] In some embodiments, the crosslinking agent contains at least three acrylate groups in its structure. The acrylate groups in the crosslinking agent react with the double bonds and the modified units in the dispersant or between the dispersant itself, thereby forming a three-dimensional crosslinked network structure between the modified conductive agent and the dispersant, thereby improving the peel strength, cohesion and flexibility of the positive electrode sheet containing the crosslinking agent.
[0051] In some embodiments, the crosslinking agent includes at least one of pentaerythritol tetraacrylate and pentaerythritol triacrylate. By selecting the crosslinking agent to react with the dispersant and the modifying unit, the positive electrode sheet forms a higher crosslinking density, ensuring higher cohesion and peel strength.
[0052] In some embodiments, the mass of the dispersant accounts for 0.1% to 0.3% of the solid mass in the positive electrode material layer, which can ensure the comprehensive performance of the positive electrode material layer, so that the slurry forming the positive electrode material layer has a high solid content, and the prepared electrode sheet has higher peel strength and cohesion.
[0053] The amount of the cross-linking agent added is 10% to 30% of the molar ratio of the dispersant, so that a higher cross-linking density can be formed between the positive electrode material layer and the conductive coating 2, ensuring higher peel strength and cohesion.
[0054] In some embodiments, the conductive coating 2 further includes a first binder, the first binder includes polyacrylate, and the mass ratio of the conductive agent with a surface modified with a modified unit in the conductive coating 2 to the first binder is 1:(0.9~1).
[0055] Specifically, the solid content of the slurry for preparing the conductive coating 2 is 15% to 20%.
[0056] In some embodiments, the positive electrode material layer further includes a second binder and an initiator. The second binder may be a common positive electrode binder in the art, such as polyvinylidene fluoride (PVdF), etc. The initiator is preferably selected from the above-mentioned silane coupling agent containing double bonds.
[0057] In a second aspect, an embodiment of the present application provides a secondary battery, comprising a negative electrode sheet, an electrolyte, and the positive electrode sheet as described above.
[0058] The present invention is further described below by way of examples.
[0059] The positive electrode slurry, the positive electrode sheet, and the secondary battery disclosed in the present invention are specifically described.
[0060] Example 1
[0061] Dispersants
[0062] 500 parts of ethanol, 15 parts of acrylamide, 15 parts of butyl acrylate and 50 parts of polyethylene glycol dimethacrylate were mixed under nitrogen, and stirred at a speed of 80 r / min for 10 min to obtain a mixed solution;
[0063] The mixed solution was heated to 50°C under a nitrogen atmosphere, and then 9 parts of azobisisobutyronitrile were added, kept at 50°C, and stirred continuously at a speed of 60 r / min. The reaction was stopped after 24 hours. 600 parts of N-methylpyrrolidone were added to the obtained polymer solution and heated and rotary evaporated to remove ethanol to obtain a dispersant with a molecular weight of 10,000-20,000 g / mol. T g is 35℃.
[0064] Cathode material layer slurry
[0065] The positive electrode material layer slurry includes 96.75 parts of lithium iron phosphate, 1 part of conductive carbon black, 0.2 parts of dispersant, 0.03 parts of cross-linking agent pentaerythritol tetraacrylate, 0.02 parts of coupling agent vinyl trimethoxy silane, and 2 parts of adhesive polyvinylidene fluoride (PVdF).
[0066] The binder and the dispersant are mixed to form a glue solution, lithium iron phosphate and conductive carbon black are added to the glue solution, and the mixture is stirred to obtain a mixed solution, pentaerythritol tetraacrylate is added to the mixed solution, and the positive electrode sheet is obtained after dispersion, and the solid content of the positive electrode slurry is 67.91%.
[0067] Preparation of conductive coating slurry
[0068] Ethanol, water and conductive carbon black are mixed to obtain a mixed solution, silane coupling agent vinyl trimethoxy silane is added to the mixed solution, and after dispersion, the solution is sand-milled for 1 minute by a sand mill, and a binder polyacrylate is added, and the mixture is stirred and sand-milled for 2 hours to obtain a conductive coating 2 slurry.
[0069] Preparation of positive electrode
[0070] The conductive coating 2 slurry is coated on both surfaces of the positive electrode current collector 1 Al foil and then dried. The positive electrode material layer slurry is coated on the surface of the conductive coating 2, and the coating surface density is controlled to be 280g / m on a single side. 2 , compaction 2.5g / m 3 , and then after cold pressing, slitting and other processes, the positive electrode sheet is obtained.
[0071] Preparation of negative electrode
[0072] 1.5% of binder SBR, 96% of negative electrode active material graphite, 1% of negative electrode conductive agent conductive carbon black, and 1.5% of thickener sodium carboxymethyl cellulose were mixed, and deionized water was added for stirring to prepare negative electrode slurry. Then the negative electrode slurry was coated on both surfaces of the Cu foil of the negative electrode current collector, and after drying, cold pressing, slitting and other processes, the negative electrode sheet was obtained.
[0073] Secondary battery preparation
[0074] The negative electrode sheet, isolation film (PE film), and positive electrode sheet are stacked in order, with the isolation film placed between the positive and negative electrodes to play an isolating role, to form an electrode assembly, which is placed in an outer package, injected with commercially available electrolyte and packaged, and then subjected to processes such as liquid injection, formation, and exhaust to obtain a secondary battery.
[0075] Example 2
[0076] Most of the steps of Example 2 are the same as those of Example 1, except that the crosslinking agent is ethylene glycol diacrylate. The solid content of the positive electrode slurry is 67.89%.
[0077] Example 3
[0078] Most of the steps of Example 3 are the same as those of Example 1, except that the crosslinking agent is acrylic acid. The solid content of the positive electrode slurry is 67.64%.
[0079] Example 4
[0080] Most of the steps of Example 4 are the same as those of Example 1, except that the crosslinking agent is pentaerythritol triacrylate. The solid content of the positive electrode slurry is 67.86%.
[0081] Example 5
[0082] Most of the steps of Example 5 are the same as those of Example 1, except that the amount of the crosslinking agent added is 0.09 parts of pentaerythritol tetraacrylate. The solid content of the positive electrode slurry is 67.32%.
[0083] Example 6
[0084] Most of the steps of Example 6 are the same as those of Example 1, except that the amount of the crosslinking agent added is 0.01 parts of pentaerythritol tetraacrylate. The solid content of the positive electrode slurry is 67.56%.
[0085] Example 7
[0086] Most of the steps of Example 7 are the same as those of Example 1, except that the amount of dispersant added is 0.1 parts, and the solid content of the positive electrode slurry is 65.01%.
[0087] Example 8
[0088] Most of the steps of Example 8 are the same as those of Example 1, except that the amount of dispersant added is 0.5 parts, the amount of cross-linking agent added is 0.09 parts, and the solid content of the positive electrode slurry is 68.55%.
[0089] Example 9
[0090] Most of the steps of Example 9 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of polyethylene glycol dimethacrylate and 30 parts of acrylonitrile, the molecular weight of the dispersant is 10000-20000 g / mol, and T g is 38℃.
[0091] The solid content of the positive electrode slurry is 67.82%.
[0092] Example 10
[0093] Most of the steps of Example 10 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of poly(propylene glycol) dimethacrylate, 15 parts of acrylamide and 15 parts of butyl acrylate, the molecular weight of the dispersant is 10000-20000 g / mol, T g The temperature is 39° C. The solid content of the positive electrode slurry is 67.64%.
[0094] Embodiment 11
[0095] Most of the steps of Example 11 are the same as those of Example 1, except that the raw material composition of the dispersant includes 30 parts of polyethylene glycol dimethacrylate, 15 parts of acrylamide and 15 parts of butyl acrylate, the molecular weight of the dispersant is 5000-10000 g / mol, and the Tg is 48° C. The solid content of the positive electrode slurry is 65.82%.
[0096] Example 12
[0097] Most of the steps of Example 12 are the same as those of Example 1, except that the raw material composition of the dispersant includes 90 parts of polyethylene glycol dimethacrylate, 15 parts of acrylamide and 15 parts of butyl acrylate, the molecular weight of the dispersant is 25000-35000 g / mol, and T g The temperature is 19° C. The solid content of the positive electrode slurry is 64.89%.
[0098] Example 13
[0099] Most of the steps of Example 13 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of polyethylene glycol dimethacrylate, 5 parts of acrylamide and 5 parts of butyl acrylate, the molecular weight of the dispersant is 10000-20000 g / mol, and T g The temperature is 39° C. The solid content of the positive electrode slurry is 64.77%.
[0100] Embodiment 14
[0101] Most of the steps of Example 14 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of polyethylene glycol dimethacrylate, 40 parts of acrylamide and 40 parts of butyl acrylate, the molecular weight of the dispersant is 10000-20000 g / mol, T g The temperature is 42° C. The solid content of the positive electrode slurry is 65.78%.
[0102] Embodiment 15
[0103] Most of the steps of Example 15 are the same as those of Example 1, except that the raw material composition of the dispersant includes 10 parts of polyethylene glycol dimethacrylate, 15 parts of acrylamide and 15 parts of butyl acrylate, the molecular weight of the dispersant is 3000-8000 g / mol, T g The temperature is 21° C. The solid content of the positive electrode slurry is 64.45%.
[0104] Example 16
[0105] Most of the steps of Example 16 are the same as those of Example 1, except that the raw material composition of the dispersant includes 50 parts of polyethylene glycol dimethacrylate, 2.5 parts of acrylamide and 2.5 parts of butyl acrylate, the molecular weight of the dispersant is 10000-20000 g / mol, T g The temperature is 25° C. The solid content of the positive electrode slurry is 64.76%.
[0106] Embodiment 17
[0107] Most of the steps of Example 15 are the same as those of Example 1, except that the silane coupling agent is 3-(trimethoxysilyl)propyl acrylate. The solid content of the positive electrode slurry is 67.98%.
[0108] Comparative Example 1
[0109] Most of the steps of Comparative Example 1 are the same as those of Example 1, except that the silane coupling agent vinyltrimethoxysilane is not added to the conductive coating slurry. The solid content of the positive electrode slurry is 67.95%.
[0110] Comparative Example 2
[0111] Most of the steps of Comparative Example 2 are the same as those of Example 1, except that the positive electrode material layer does not contain a cross-linking agent, and the solid content of the positive electrode slurry is 67.57%.
[0112] Comparative Example 3
[0113] Most of the steps of Comparative Example 3 are the same as those of Example 1, except that plain foil is used for coating, and the solid content of the positive electrode slurry is 67.91%.
[0114] Comparative Example 4
[0115] Comparative Example 4 is similar to Example 1 in most steps, except that the dispersant is N-methylpyrrolidone dispersion of polyvinylpyrrolidone. The solid content of the positive electrode slurry is 64.98%.
[0116] Slurry, pole piece, electrical performance test:
[0117] The slurries, positive electrode sheets, and secondary batteries prepared in the above examples and comparative examples were subjected to the following tests.
[0118] 1) Slurry solid content: Spread the slurry evenly on the surface of aluminum foil, bake and heat it using a solid content meter until it stops losing weight, and record the data at this time.
[0119] 2) Slurry viscosity: The viscosity value is measured at room temperature using a rotational viscometer, 4# rotor, 60 rpm; the 24h viscosity is measured after the slurry is sealed and placed in a φ5cm×15cm bottle for 24 hours.
[0120] 3) Positive electrode peel strength test:
[0121] The coated single-sided positive electrode sheet was heated to 2.4 g / cm 3 After compaction, a tensile testing machine with a range of 20N was used. The electrode was cut into 20cm long and 3cm wide. 3M double-sided tape was attached to the steel plate. The electrode coating was fixed on the tape on the steel plate with the surface facing down. After rolling back and forth 6 times with a 2.5kg roller, the coating and aluminum foil were torn off. The upper plate clamped the aluminum foil side and stretched at a speed of 50mm / min and 180°C. The data of the stable tension section was recorded as the peel strength (N / m).
[0122] 4) Flexibility test
[0123] A tensile testing machine with an existing range of 20N was used, and the machine was switched to the downward pressing mode. The 1.5*12cm cold-pressed pole piece was rolled into a circle and placed in a homemade steel plate fixture. The instrument descending speed was set to 20mm / min. The instrument continuously applied force to the circular pole piece during the downward pressing stroke until the pole piece arc broke. The flexibility of the pole piece can be determined by the downward pressing stroke and the force at the time of breaking.
[0124] 5) Cohesion test
[0125] The coated single-sided positive electrode sheet was heated at 2.4 g / cm 3 After compaction, a tensile testing machine with a range of 20N was used. The electrode was cut into 20cm long and 3cm wide. 3M double-sided tape was attached to the steel plate. The electrode coating side was fixed on the tape on the steel plate with the coating side facing up. After rolling back and forth 6 times with a 2.5kg roller, the coating and aluminum foil were torn off. The upper plate clamped the coating surface and stretched at a speed of 50mm / min and 180℃. The data of the stable tension section was recorded as the peel strength (N / m).
[0126] 6) 25℃, DCIR test
[0127] ① Charge at 0.5C constant current and constant voltage to 3.65V, with a cut-off current of 0.05C; discharge at 0.5C constant current to 2.5V, and record the discharge capacity; repeat the above for 5 weeks, and take the discharge capacity in the 5th week as C0;
[0128] ② Charge at 1C constant current and constant voltage to 3.65V, with a cut-off current of 0.05C; discharge at 1C constant current to 50% SOC, and record the voltage V0 after standing for 2 hours; discharge at 1C constant current for 10s, and record the discharge end voltage V1; charge at 1C constant current for 10S.
[0129] Discharge DCIR = (static terminal voltage V0 before discharge - discharge terminal voltage V1) / discharge current 1C.
[0130] 7) Normal temperature cycle test
[0131] The specific method is: after placing the battery in a constant temperature test room at 25℃±2℃ for 1h, charge it to 3.65V at 1C constant current and constant voltage, with a cut-off current of 0.05C; discharge it to 2.5V at 1C constant current, and record the discharge capacity; repeat the above steps 500 times, and calculate the capacity retention rate.
[0132] Table 1
[0133]
[0134] 1) By comparing Example 1 with Comparative Example 1, it can be seen that the conductive agent without adding a coupling agent to modify the conductive coating cannot form a three-dimensional network structure between the conductive layer and the active material coating, resulting in a significant decrease in the electrode peeling strength.
[0135] 2) By comparing Example 1 and Comparative Example 2, it can be seen that no cross-linking agent is added to the slurry of Comparative Example 2, so the dispersant in the active coating cannot cross-link itself, and cannot cross-link with the conductive agent in the conductive coating modified by the coupling agent, resulting in a significant decrease in the cohesion and peel strength of the electrode.
[0136] 3) By comparing Example 1 and Comparative Example 3, it can be seen that the use of plain foil for coating results in the substrate being unable to form a three-dimensional network cross-linked structure with the active material coating, and the electrode peeling strength and flexibility, as well as the coating cohesion are significantly reduced.
[0137] 4) By comparing Example 1 and Comparative Example 4, it can be seen that Comparative Example 4 uses PVP as a dispersant, the solid content of the slurry is limited, the 24h viscosity increases significantly, and the electrode peeling strength and flexibility, and the coating cohesion are poor.
[0138] 5) From the comparison of Examples 1, 2, 3, and 4, it can be seen that the more acrylate functional groups a cross-linking agent contains, the greater its degree of cross-linking, and the more obvious the improvement in the flexibility and cohesion of the electrode, which in turn affects the DCIR of the battery cell and the cycle capacity retention rate. This indicates that the more acrylate units there are in the cross-linking agent, the greater the probability of cross-linking, thereby enhancing the three-dimensional network skeleton structure.
[0139] 6) By comparing Examples 1, 5, and 6, it can be seen that the cross-linking effects are different at different contents. When the amount of the cross-linking agent used is reduced to 0.01 parts outside the lower limit, the cross-linking probability between the active coatings and between the active coatings and the conductive coatings decreases, and the cross-linking effect is not obvious, resulting in cracking of the electrode, and decreased flexibility and cohesion. When the amount of the cross-linking agent used is the upper limit of 0.09 parts, although the peel strength, flexibility, and cohesion of the electrode can be maintained at a high level, more acrylate units in the cross-linking agent will react with the electrolyte components, deteriorating the battery performance, increasing the DCIR of the battery cell and reducing the capacity retention rate.
[0140] 7) By comparing Examples 1, 7, and 8, it can be seen that when the amount of dispersant used is reduced to 0.1 part, it has a greater impact on the increase in the solid content of the slurry and the 24h viscosity stability. The decrease in the amount of dispersant used leads to a decrease in the cross-linking degree of the cross-linking agent and the conductive coating, which reduces the peel strength, flexibility, and cohesion of the electrode.
[0141] 8) From the comparison of Examples 1, 9, and 10, it can be seen that the dispersants formed by copolymerization of other types of polyesters and anchoring groups have little overall difference in improving the solid content of the slurry, the 24h viscosity stability, and the electrode characteristics, indicating that other polyesters and anchoring groups can also achieve similar effects.
[0142] 9) Examples 1, 11, 12, and 15 compare the effects of different amounts of polyester on molecular weight. It can be seen that when the proportion of poly(ethylene glycol) diacrylate is too high, the molecular weight is relatively large, and the dispersion of LFP or conductive agent is mainly due to steric hindrance effect. The effect on the dispersibility and solid content of the slurry is not obvious, and the 24-hour static viscosity of the slurry increases significantly. The flexibility and cohesion of the pole piece also tend to decrease, the DCIR of the battery cell increases, and the cycle capacity retention rate decreases; when the proportion of poly(ethylene glycol) diacrylate is too low, the molecular weight of the dispersant is low, and the dispersion and stabilization effect of the pole piece on the slurry is mainly the effect of the anchoring group. The increase in the solid content of the slurry is limited, and the 24-hour static viscosity of the slurry increases significantly. The reduction in the proportion of polyester also reduces the probability of cross-linking reaction with the conductive agent in the conductive coating. Therefore, it affects the peel strength, cohesion, flexibility, DCIR of the battery cell, and cycle performance of the pole piece. Therefore, when the ratio of the anchoring group and the polyester copolymer is moderate, the steric hindrance effect of the dispersant and the ionic bond of the anchoring group can act together on the surface of the dispersed material, thereby increasing the solid content of the slurry and maintaining the slurry stability for 24 hours.
[0143] 10) By comparing Examples 1, 13, 14, and 16, it can be seen that the effect of the amount of anchoring groups used is compared. It can be seen that when the content of anchoring groups is too high, the improvement of the dispersibility of the slurry is mainly due to the effect of the anchoring groups, so the increase in the solid content of the slurry is small, and it has a certain effect on the peeling strength, flexibility, and cohesion of the electrode; when the content of anchoring groups is too low, the improvement of the dispersibility of the slurry is mainly due to the steric hindrance effect of polyester, resulting in an insignificant increase in the solid content of the slurry, and it has a certain effect on the peeling strength, flexibility, and cohesion of the electrode. Therefore, when the ratio of anchoring groups and polyester copolymers is moderate, the steric hindrance effect of the dispersant and the ionic bond of the anchoring groups can act together on the surface of the dispersed material, thereby increasing the solid content of the slurry and maintaining the stability of the slurry for 24 hours.
[0144] 11) By comparing Examples 1 and 17, it can be seen that the conductive agent in the conductive coating modified with other silane coupling agents can achieve the same effect.
[0145] It can be seen that the dispersant with moderate molecular weight prepared by the method, its steric hindrance effect and the ionic bond of the anchoring group act together on the surface of the dispersed material, so that the slurry has a better dispersion effect, improves the solid content of the slurry and maintains the stability of the slurry for 24 hours; different contents of acrylate units in the cross-linking agent and the amount added have a certain influence on the cross-linking degree and cross-linking network structure of the conductive coating and the active material coating, thereby affecting the peeling strength, cohesion and flexibility of the electrode, and when the amount of cross-linking agent added is too high, there is a risk of incomplete reaction with the electrolyte, thereby affecting the cycle performance of the battery cell; the conductive agent in the conductive coating modified by the coupling agent can ensure a higher probability of cross-linking with the active material coating, thereby improving the peeling strength, cohesion and flexibility of the electrode, thereby reducing the DCIR of the battery cell and improving the cycle performance of the battery cell; the bare foil cannot form a three-dimensional network cross-linking structure with the active coating, resulting in a decrease in its electrode peeling strength, cohesion and flexibility.
[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a current collector and a positive electrode material layer, wherein the positive electrode material layer is arranged on at least one side of the current collector; the current collector comprises a current collector body and a conductive coating, wherein the conductive coating is arranged on at least one side of the current collector body, and the conductive coating comprises a second conductive agent, wherein the surface of the second conductive agent is modified with a silane coupling agent containing double bonds; The positive electrode material layer includes a positive electrode active material, a first conductive agent, a dispersant and a cross-linking structure, wherein the dispersant is wrapped on the surface of the positive electrode active material and the conductive agent, and the cross-linking structure is used for chemical bonding between the dispersants and chemical bonding between the dispersant and the conductive agent in the conductive coating on the surface of the current collector; The dispersant comprises a polymer segment and an anchoring group connected to the polymer segment, wherein the polymer segment comprises an acrylate-polyol unit, and the terminal group of the polymer segment is an acrylate group; the anchoring group comprises one or more of a nitrile group, an amide group, an ester group, a carboxyl group and a hydroxyl group; the terminal group of the dispersant is an acrylate group, and the terminal group and the silane coupling agent containing a double bond are respectively combined with a crosslinking agent to form the crosslinking structure; The cross-linking agent includes at least one of pentaerythritol tetraacrylate and pentaerythritol triacrylate; The dispersant is obtained by reacting a raw material composition comprising an acrylate-polyol monomer and an anchor group-containing monomer; the molar ratio of the anchor group-containing monomer to the acrylate-polyol monomer is (10-50): (20-70); The molecular weight of the dispersant is 10000-20000 g / mol, T g 25℃~45℃; The mass of the dispersant accounts for 0.2% to 0.3% of the solid mass in the positive electrode material layer; The molar ratio of the crosslinking agent to the dispersant is (0.1-0.3):
1.
2. The positive electrode sheet according to claim 1, characterized in that: The silane coupling agent containing double bonds includes one or more of (3-methacryloxy-2-hydroxypropoxy)propylbis(trimethylsiloxy)methylsilane, 3-(trimethoxysilyl)propyl acrylate, vinyltrimethoxysilane, and allyltrimethoxysilane.
3. The positive electrode sheet according to claim 1, characterized in that: The crosslinking agent contains at least three acrylate groups in its structure.
4. A secondary battery, characterized in that: The invention comprises a negative electrode sheet, an electrolyte and a positive electrode sheet as claimed in any one of claims 1 to 3.
Citation Information
Patent Citations
Battery electrode, preparation method thereof, and all-solid-state battery
CN109216701A
Conductive carbon slurry, positive electrode slurry, and preparation method and application of conductive carbon slurry and positive electrode slurry
CN114914402A